Sebuah Kajian Semiotika F. de Saussure: Analisis Makna Motivasi dalam Lirik Lagu Zenryoku Shounen - Virdaus, Nurica (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2024)
This research examines the motivation contained in song lyrics of Zenryoku Shounen which is based on F. de Saussure's semiotic theory. Saussure's semiotic method explains that signs have elements that are interconnected; signifier and signified. This study qualified as qualitative descriptive approach. The data used is the lyrics of the song Zenryoku Shounen by Sukima Switch. The data analysis technique used is Saussure's semiotic theory; the researcher makes an interpretation by dividing the entire song lyrics into 8 stanzas which are then analyzed to find the meaning of motivation. The results of this study, Zenryoku Shounen has a very related meaning and contained a motivational message. The motivational meanings contained in this song are: 1) the feeling of sinking and failure comes from oneself, it strengthens the shield so that it is not affected by the environment; 2) don't give up easily because of a failure; 3) to be able to move forward the steps that must be taken are to make peace (self-acceptance); 4) rising from adversity requires sacrifice and hard work; 5) if one dream fails, then many other dreams stretch out; 6) if a person is afraid to take a step, then he will get nothing in life; 7) wherever there is hope there will always be and very important for someone who is struggling to achieve a dream; and 8) after a failure, keep moving forward and have a clear view because the only one who can lead to a dream is ourself. Even if there are problems in the process, a strong determination will not get in the way.